ANALISIS WACANA KRITIS TEORI INCLUSION THEO VAN LEEUWEN DALAM BERITA KRIMINAL PEMBUNUHAN BRIGADIR JOSHUA DENGAN TERSANGKA FERDY SAMBO - Iwan Kamaludin; Agus Hamdani (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
This research analyzes the use of Theo Van Leeuwen's Inclusion Theory in criminal news concerning the murder of Brigadier Joshua on tvonenews.com, edition July 13, 2022. Data collection was conducted through three stages: (1) reading and understanding the discourse titled "Police Mentioned the Adultery Issue of Brigadier J with the Wife of Kadiv Propam Putri Ferdy Sambo Being Investigated, but..." on the tvonenews.com portal, July 13, 2022 edition, with the aim of obtaining a clear understanding of the discourse to be examined, (2) marking the parts of the discourse related to Theo Van Leeuwen's Inclusion Theory, and (3) inventorying sentences in the discourse related to Theo Van Leeuwen's Inclusion Theory using a data inventory format. The data analysis was conducted descriptively. Based on the research findings, it can be concluded that there are four out of seven theories of Theo Van Leeuwen's Inclusion Theory found in the criminal news about the murder of Brigadier Joshua on tvonenews.com, July 13, 2022 edition, namely objectivity-abstraction, nomination-categorization, nomination-identification, and association-disassociation. It can be inferred that in writing criminal news about the murder of Brigadier Joshua, the victim is marginalized by the writer. Although the journalists still conceal the identity of the actors in the news headlines, the way the news is written leads readers to perceive that the victim is the cause of all these events. Keywords: Discourse analysis, Inclusion, Theo Van Leeuwen